2016
DOI: 10.3390/ani6110066
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Suckling in Combination with an Older Weaning Age Improves Growth, Feed Intake and Aspects of Gastrointestinal Tract Carbohydrate Absorption in Pigs after Weaning

Abstract: Simple SummaryThe weaning of piglets involves abrupt changes that often cause reduced production and predisposition to gastrointestinal tract dysfunction. Increasing the weaning age or using gradual weaning are techniques that can improve post-weaning performance. In this study, it is shown that an older weaning age (day 35) in combination with intermittent suckling (daily separation of piglets from the sow for 8 h in the week before weaning) improved growth rate, feed intake and aspects of gastrointestinal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Next, cortisol levels were measured in AF and maternal plasma (collected at the day of fetal sampling) with Cortisol ELISA Kit (ADI-900-071, Enzo Life Sciences, Farmingdale, NY, USA) according to the manufacturer's instructions. The kit has been validated by the manufacturer for compatibility with porcine samples and has been previously used in pig research [22][23][24][25]. The assay detection limit was 56.7 pg/ml.…”
mentioning
confidence: 99%
“…Next, cortisol levels were measured in AF and maternal plasma (collected at the day of fetal sampling) with Cortisol ELISA Kit (ADI-900-071, Enzo Life Sciences, Farmingdale, NY, USA) according to the manufacturer's instructions. The kit has been validated by the manufacturer for compatibility with porcine samples and has been previously used in pig research [22][23][24][25]. The assay detection limit was 56.7 pg/ml.…”
mentioning
confidence: 99%
“…If so, post-weaning mannitol levels are expected to be lower than pre-weaning levels, as a reflection of a decreased intestinal surface area resulting from weaning. This seems to be in line with the numerically lower levels of mannitol after weaning compared with before weaning in our study, and similar results were found by Turpin et al (2016). However, this does not provide a satisfactory explanation for the lower plasma concentrations of mannitol (-46%) on day 5 after weaning in MS piglets compared with FC piglets, as MS piglets seemed to perform better between days 2 to 5 in terms of feed utilisation.…”
Section: Discussionsupporting
confidence: 74%
“…However, studies in which forced IS was combined with an extended lactation showed that piglets displayed more eating behaviour before weaning and showed an improved transition to the post-weaning phase, indicated by a higher feed intake, reduced growth check, improved intestinal function, and reduced aggression and damaging oral manipulation Turpin et al, 2016), compared with conventionally weaned piglets. Similarly, studies providing a piglet-free area for the sows found a higher pre-weaning feed intake, a higher post- weaning feed intake, a higher post-weaning weight gain , and more post-weaning eating behaviour (Rantzer et al, 1995) than in piglets reared with individually housed sows.…”
Section: A More Gradual Weaning Process During An Extended Lactationmentioning
confidence: 99%
See 1 more Smart Citation
“…Donors <2‐4 years of age are usually not accepted for human corneal allotransplantation . The puberty onset age of pigs is approximately 4‐5 months . Corneas from younger‐aged (<3 months) pigs were extremely soft and were more pliable than corneas from older pigs .…”
Section: Discussionmentioning
confidence: 99%